Herramientas de comunicación sincrónicas y su aporte al desarrollo de las competencias orales en inglés (2018)
Nowadays society demands the use of technology, accompanied of English knowledge. For this reason, to educational level, it is relevant and necessary that the schools notice the big benefits that the interaction of these two elements can bring about. The objective of this study consists of showing the contribution of synchronous tools in order to develop oral English skills in eleventh grade students. Theoretical basis were considered to be the authors' contributions in three categories of analysis as follows: Communicative ability, Theories of motivation and a second Language learning, and Information and communication technologies. The methodology was Investigation – Action, since in this social research the pupils participate as beneficiaries of the project and the teachers as agents of change in the search of solutions to the difficulties presented in English classes, under a mixed approach quasi-experimental descriptive type with a sample of 67 students divided in two groups, an experimental group consisting of 36 students and a control group made up of 31 students. The findings showed that in the experimental group there was a notable decrease in the low level in all the categories of analysis and therefore a significant increase in the high levels; unlike the control group, which showed a minimum decrease of the low level in most of the categories analyzed.. It was concluded that the use of synchronous tools such as videostreaming and videoconference in classroom, in conjunction with a constructivist teaching learning – model, in which students were creators of their own knowledge, increased the interest of them in the accomplishment of the activities proposed in the subject, so, it made them feel much more confident at the moment of having conversations and oral presentations and it was possible to demonstrate a better oral performance related to fluency, cohesion and coherence.